The Wiley Blackwell companion to the Qur'an - Rippin, Andrew,d1950-2016,eeditor; Mojaddedi, J. A.q(Jawid Ahmad),eeditor (Wiley-Blackwell companions to religion, 2017)
Fully revised and updated, the second edition of The Wiley Blackwell Companion to the Qur'ān offers an ideal resource for anyone who wishes to read and understand the Qur'ān as a text and as a vital component of Muslim life. While retaining the literary approach to the subject, this new edition extends both the theological and philosophical approaches to the Qur'ān. Edited by the noted authority on the Qur'ān, Andrew Rippin, and Islamic Studies scholar Jawid Mojaddedi, and with contributions from other internationally renowned scholars, the book is comprehensive in scope and written in clear and accessible language. New to this edition is material on modern exegesis, the study of the Qur'ān in the West, the relationship between the Qur'ān and religions prior to Islam, and much more. The Wiley Blackwell Companion to the Qur'ān is a rich and wide-ranging resource, exploring the Qur'ān as both a religious text and as a work of literature